2021
DOI: 10.1109/tro.2020.3047064
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Coupling Effect in Human-Commanded Stiffness During Bilateral Tele-Impedance

Abstract: Tele-impedance augments classic teleoperation by enabling the human operator to actively command remote robot stiffness in real-time, which is an essential ability to successfully interact with the unstructured and unpredictable environment. However, the literature is missing a study on benefits and drawbacks of different types of stiffness command interfaces used in bilateral tele-impedance. In this article, we introduce a term called coupling effect, which pertains to the coupling between human-commanded sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Unlike the state-of-the-art interfaces based on EMG [1], grip force [2] and button [5], the voice-based impedance command interface does not require a limb to operate it and is essentially a hand-free approach. It was shown that the EMGbased interfaces have a coupling effect between between the force feedback (if implemented) and the commanded stiffness; i.e., physical interaction with the limb of the human operator can affect the commanded impedance [26]. Since the proposed method is based on vision and voice, there is no direct physical contact between the human limb and the impedance-command interface and such effect is not present.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the state-of-the-art interfaces based on EMG [1], grip force [2] and button [5], the voice-based impedance command interface does not require a limb to operate it and is essentially a hand-free approach. It was shown that the EMGbased interfaces have a coupling effect between between the force feedback (if implemented) and the commanded stiffness; i.e., physical interaction with the limb of the human operator can affect the commanded impedance [26]. Since the proposed method is based on vision and voice, there is no direct physical contact between the human limb and the impedance-command interface and such effect is not present.…”
Section: Discussionmentioning
confidence: 99%
“…A potential disadvantage of the proposed interface is that it could require more attention from the human operator and might therefore be less intuitive compared to some of the existing interfaces. Using EMG [5], [9], EIT [15] or grip-force [11] based interfaces, the human might naturally contract its muscles based on the situation in the remote environment, which in turn would change the remote robot's endpoint stiffness, as shown in [21]. Therefore, the proposed method might be more suitable for application in space or industrial robotics, where changes tend to be slower, while the above-mentioned methods might be more suitable for application in robotic surgery, where quick stiffness changes are crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ability to command the size, shape and orientation of the stiffness ellipsoid to the robot is limited. In addition, it has been shown that there is a coupling effect between the interaction force at the haptic interface and human commanded stiffness in EMG-based tele-impedance [21]. Furthermore, these approaches typically involve a complex setup (including issues related to wearable devices [22], [23]) and a time-consuming calibration process, which is another key disadvantage in terms of applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the changes in EMG and grip force are not only due to the limb impedance (i.e., to the stiffness and damping parameters) but are person specific, and also due to: limb motion trajectory, body posture and time (fatigue). Therefore, while EMG or grip force may still be good methods to estimate impedance in the absence of perturbations, they require user-specific calibration [21], [22]. On the other hand, in the presence of external perturbations, particularly continuous and non-repetitive ones, EMG and grip force signals include muscle reflexes, which are characterized by their own temporal and state dynamics [22] making impedance estimation non trivial.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while EMG or grip force may still be good methods to estimate impedance in the absence of perturbations, they require user-specific calibration [21], [22]. On the other hand, in the presence of external perturbations, particularly continuous and non-repetitive ones, EMG and grip force signals include muscle reflexes, which are characterized by their own temporal and state dynamics [22] making impedance estimation non trivial.…”
Section: Introductionmentioning
confidence: 99%